Research Progress of Modification for Peelable Coating - LEI Rui - cheng, WANG Yang, LIU Lan - xuan, LI Dong - dong, FENG Zeng - hui, ZHANG Zhe, LIU Xiu - sheng (Cailiao Baohu, 2021)
Using peelable paint to temporarily protect the surface of an object is an effective means to solve the problems of bumps, scratches and pollution on the surface of various objects. In this work, the types and characteristics of peelable coatings, outlines the research progress of various peelable coating modification technologies were summarized, and the development direction of peelable coating modification research was forecasted.